An ecological study of Tarchonanthus camphoratus L. in the Northern Cape Province of South Africa - Stehn, Imke Jutta (University of the Free State, 2020)
Bush-thickening resulting in decreased agricultural productivity, inaccessible thickets and increased occurrence of pseudo-droughts is a common phenomenon in the semi-arid southern African savanna. Until recently, land owners paid little attention to T. camphoratus, but there is a growing awareness of the potential threat that this species presents, largely because it (1) increased significantly in numbers during the past few decades, (2) reduces the productivity of the herbaceous layer, (3) is semi-deciduous to evergreen, thus requiring water all year round in a water-limited environment, (4) is a less palatable woody plant species, (5) reproduces sexually and asexually and (5) is fire tolerant. The main objective of this study was to gain a better understanding of the ecological functioning of T. camphoratus to establish objective guidelines for the effective and ecologically responsible management of the species. The research was conducted in the Kimberley Thornveld on Rooipoort Nature Reserve in the Northern Cape Province on deep sandy soil and on shallow rocky soil. The influence of T. camphoratus on the soil nutrient status, its leaf and reproductive phenology, as well as shoot growth in relation to different climate variables, including temperature, day length and rainfall and its coppicing ability as influenced by season of disturbance, were studied. The existence of a soil seed bank and allelopathic effects in the soil, the effect of soil originating from different subhabitats on seedling growth and the response of T. camphoratus and co-dominant Senegalia mellifera to fire were also investigated. In addition, seed production was quantified and regression equations relating spatial canopy volume to leaf and wood biomass were developed from harvested undamaged and coppicing plants. It was established that, although some nutrients, including potassium, total nitrogen and organic carbon, differed significantly between the two soil types, the soil under the canopies of T. camphoratus had a higher soil nutrient status compared to soil in the open grassland. Climate, especially temperature and rainfall, were strongly correlated with the leaf carriage and shoot growth of T. camphoratus. T. camphoratus retained more leaves during the dry period compared to other woody species in the area. All T. camphoratus shrubs coppiced after cutting. However, shrubs cut during the active growth season (summer) coppiced less vigorously compared to those cut during winter.The seed production of female T. camphoratus shrubs was relatively high (40 469 ± 4504 seeds ETTE-1), but seeds did not persist in the soil seed bank for longer than one year. High seed densities of other plants, especially grasses, in the soil under the canopies of T. camphoratus suggested a high restoration potential in terms of herbaceous plant establishment, where T. camphoratus was removed in bush-thinning operations. No allelopathic effects limiting seed germination and seedling growth were evident. The seeds of T. camphoratus underwent a three- to four-month dormancy period before they germinated. Seedlings grew more vigorous in the nutrient-rich soil originating from the canopied subhabitat compared to the nutrient-poor soil originating from the open grassland. This has implications for tree-thinning operations, as areas where mature trees are removed may subsequently present ideal areas for the establishment and growth of T. camphoratus seedlings. Furthermore, it was found that T. camphoratus recovered more rapidly than S. mellifera after a hot fire and that, in areas where these two species are co-occurring, frequent fires may eventually result in the replacement of S. mellifera by T. camphoratus. Highly significant (p < 0.001) regression models with very high coefficients of determination (r > 0.8) relating spatial canopy volume to dry mass fractions of leaves and stems in three diameter classes (< 5 mm, 5 – 20 mm and > 20 mm) were developed for undamaged and coppicing T. camphoratus shrubs. This will enable the accurate assessment of the phytomass for research purposes, wildlife management and biofuel production estimates. The positive attributes of T. camphoratus that include soil enrichment under their canopies, the provision of valuable browse during dry periods when deciduous woody species are leafless and a high density and species-rich seed bank in the soil under their canopies that ensure a high restoration potential after bush-thinning, may not be overlooked. Depending on the management objective, restoration of bush-thickened areas must take cognisance of the soil type, reproductive phenology (fruit maturation) and seasonal response of T. camphoratus to mechanical damage, as these may play an important role in the success of thinning operations and recruitment period influencing duration between follow-up treatments.
Dissertation (M.Sc. (Animal, Wildlife and Grassland Sciences))--University of the Free State, 2020
Keywords: Allometric; Bush-thickening; Coppicing ability; Fire; Phenology; Seed production; Seedling establishment; Shoot growth; Soil nutrients; Soil seed bank; Tarchonanthus camphoratus